2012
DOI: 10.1111/j.1365-313x.2012.05003.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal cell differentiation in cotton mediated by the homeodomain leucine zipper gene, GhHD‐1

Abstract: SUMMARYGossypium hirsutum L. (cotton) fibres are specialized trichomes a few centimetres in length that grow from the seed coat. Few genes directly involved in the differentiation of these epidermal cells have been identified. These include GhMYB25-like and GhMYB25, two related MYB transcription factors that regulate fibre cell initiation and expansion. We have also identified a putative homeodomain leucine zipper (HD-ZIP) transcription factor, GhHD-1, expressed in trichomes and early fibres that might play a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
149
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(154 citation statements)
references
References 49 publications
(73 reference statements)
5
149
0
Order By: Relevance
“…Previously, GhHD1 was postulated to be related to trichome formation and fiber initiation by gene silencing and gene expression (Walford et al 2012). In the present research, a Ty1-copia retrotransposon was found inserted into At-GbHD1 that blocks its expression.…”
Section: Hd1 Is Critical To Stem Trichome Growth In Gossypiummentioning
confidence: 57%
See 2 more Smart Citations
“…Previously, GhHD1 was postulated to be related to trichome formation and fiber initiation by gene silencing and gene expression (Walford et al 2012). In the present research, a Ty1-copia retrotransposon was found inserted into At-GbHD1 that blocks its expression.…”
Section: Hd1 Is Critical To Stem Trichome Growth In Gossypiummentioning
confidence: 57%
“…We now know that this difference is closely associated with the disruption of the At-HD1 gene in G. barbadense. Since HD1 is also involved in fiber development (Walford et al 2012), we speculated that this insertion could be one of the main reasons why most G. barbadense varieties have little or no fuzz fiber. The association between the TE insertion, the glabrous stem, and fuzz-less seeds is being investigated in our laboratory.…”
Section: Hd1 Is Critical To Stem Trichome Growth In Gossypiummentioning
confidence: 99%
See 1 more Smart Citation
“…The focus of Australian transgenic R&D work has been on developing potential traits of more specific relevance to the Australian Industry and on basic research to understand gene function, particularly the functions of genes involved in fibre initiation and formation, plant defence and seed oil formation. Such work has demonstrated the importance of GhMyb 25 [64], GhMyb25-like [65] and GhHD-1 [66] for fibre initiation and for controlling fibre initial numbers. As part of CSIRO research, transgenic cotton plants that are altered in the expression of GhMYB109 were imported under a Material Transfer Agreement for research use [67].…”
Section: Transgenicsmentioning
confidence: 98%
“…Members of the HD-ZIP IV family were shown to regulate cuticle metabolism in tomato and maize (Zea mays), including CUTIN DEFICIENT2 (CD2; Isaacson et al, 2009;Nadakuduti et al, 2012) and OUTER CELL LAYER1 (Javelle et al, 2010;Depège-Fargeix et al, 2011), respectively. Other HD-ZIP IV proteins, including the Arabidopsis GLABRA2 (AtGL2; Rerie et al, 1994;Ishida et al, 2007;Tominaga-Wada et al, 2009, PROTODERMAL FACTOR2 (AtPDF2; Abe et al, 2003), Arabidopsis HOMEODOMAIN GLABROUS11 (Nakamura et al, 2006), MERISTEM LAYER1 (AtML1; Abe et al, 2003;Takada et al, 2013), and cotton (Gossypium hirsutum) HOMEODOMAIN1 (Walford et al, 2012), were shown to be involved in the regulation of epidermal cell differentiation. Two members of the SHN1/WIN1 clade of transcription factors from Arabidopsis and tomato (AtSHN1 and SlSHN3, respectively) have been shown to be required for both cutin biosynthesis as well as epidermal cell patterning (Aharoni et al, 2004;Broun et al, 2004;Shi et al, 2011Shi et al, , 2013.…”
mentioning
confidence: 99%